HOUSEHOLD PARTICIPATION IN RECYCLING PROGRAMS: A CASE STUDY FROM MALAYSIA - Azilah M Akil; Foziah Johar; Ho Chin Siong (Diponegoro University, 2015)
The increase in per capita income and rapid urbanization, have contributed significantly to changes in consumption behaviour leading to increased waste generation. Waste disposed to landfill sites is fast becoming unfeasible thus requiring a more effective management of waste material involving waste reduction, reuse and recycling. The success of recycling program, however, is largely dependent on household participation activities which are essentially behaviour driven. The recycling performance of Malaysian households is still low as it stands at 5.5% compared to Singapore and Vietnam which are 56% and 22% respectively. This study examines recycling behaviour among households and the influence of socioeconomic, demographic and behavioural characteristics on households’ participation in recycling program in Malaysia. A sample of 300 randomly selected household were surveyed. The findings revealed that most of the households (70%) claim that they are practicing recycling particularly types of paper and old clothes. The factors of participation in recycling show equal results both for environmental concerns and economic benefits. Those who did not participate in recycling, listed household issues or behaviour, namely lack of time and materials to recycle, inconvenient, lack of space, lack of facilities and information as well as laziness, as barriers. The paper finally highlights the factors which can encourage household to be involved in recycling and give recommendations to the authorities in terms of facilities and infrastructures to facilitate the program.